O Mundo Clássico e a Universalidade dos seus Valores (Coimbra University Press, 2025)
This work aims to honor Prof. Doctor Nair de Nazaré Castro Soares, Emerita Professor of the University of Coimbra, in recognition for her brilliant academic career and outstanding achievements in the research and teaching throughout the years. Many generations of students and researchers have benefited, in the country and abroad, from her long and profitable activity at the service of university and science. This work results from the contributions of those disciples, colleagues and friends, gathering studies that cover the main areas of knowledge in which she excelled: Greco-Roman Literature and Culture, Classical Tradition in the Middle Ages, studies on Renaissance Humanism, and Classical Heritage in Modern and Contemporary World.